Upper Cretaceous and Paleocene calcareous nannoplankton from the Soča Valley - Pavšič, Jernej (Geologija, 1979)
In Upper Cretaceous and Paleocene beds of flysch and of Podsabotin beds in the Soča Vallev 108 species of calcareous nannoplankton were determined. The species are moderately well preserved, and they occur in the time interval from the Campanian stage to the Eocene epoch. On the basis of determined species 12 nannoplankton biozones were recognized. The Cretaceous/Tertiary boundary was defined in a flysch sequence at Čolnica village in Littoral Slovenia.